Complex control of sport training of javelin throwers on the stages of specialization and sports improvement. - Tsipovіaz A.T; Bondarenko Н.M (Kharkov National Pedagogical University, 2011)
The ample opportunities of application of the instrumental estimation methods of javelin throwers' technical and special running training are considered. 10 qualified javelin throwers took part in the experiment. In the research a tensometric spear was used for the identification of speed and force increase character in phase of final effort. It is proved, that gradual speed increase without significant decline and rippling in phase of "traction" and impetuous force increase in "burst" phase of final effort characterize modern technique and proper special-power training. Special running training control is exercised by the results of 20 meters running in motion and 20 meters running with spear draw aside.